Does the social equitability of community and incentive based conservation interventions in non-OECD countries, affect human well-being? A systematic review protocol. Issue 1 (December 2016) - Althor, Glenn; McKinnon, Madeleine; Cheng, Samantha; Klein, Carissa; Watson, James
Abstract Background An increasing number of conservation interventions aim to reduce their negative impacts on vulnerable people and to provide incentives aimed at improving overall human well-being. Community and incentive based conservation interventions have had variable rates of success in producing well-being outcomes, yet it is unclear why. Researchers have hypothesised that socially equitable conservation interventions will improve their likelihood of success. However, for community and incentive based interventions, there is a lack of evidence synthesis for the effect that social equity has on human well-being outcomes. Using this protocol, we will undertake a systematic review of relevant literature with the aim of using existing knowledge to address this gap. Methods This protocol outlines the methodology we will use to examine the research question:Does the social equitability of community and incentive based conservation interventions in non -OECD countries, affect human well -being? We will conduct a systematic review of available studies, using articles that measure the effect of social equity, defined as the absence of avoidable and unfair, cost and benefit distributions between socially stratifying factors. To make this process efficient, and in order to prevent replication, we will utilize and update a literature search, and sub-set of data, collected in a previous systematic map that assessed the quantity and strength of evidence to support the effects conservation interventions have on human wellbeing. We will critically appraise each study we identify and capture the degree to which interventions integrated social equity within project participation and outcomes. Where integrated, we will determine if studies record or describe the effect that social equity had on human well-being. We have developed a conceptual framework that describes the expected effect of social equity, in order to capture and understand these effects. To understand the strength of relationships in our framework, and where data availability allows, we will undertake and combine a series of qualitative and quantitative data syntheses. By undertaking this study, we intend to understand how social equity considerations, specifically within community and incentive based conservation interventions, can affect human well-being. A better understanding of these features will inform conservation practitioners and researchers on the extent to which they ought to incorporate social equity into interventions in order to promote human well-being.